Evaluating the necessity of booster sessions in relapse prevention for depression: a longitudinal study - Jón Ingi Hlynsson; Jón Ingi Hlynsson; Tómas Kristjánsson; Gerhard Andersson; Gerhard Andersson; Gerhard Andersson; Per Carlbring; Per Carlbring; the ACTUA research group (Frontiers in Psychology, 2025)
IntroductionMajor depression is a highly prevalent and heterogenous mental disorder. Although therapeutic advances for major depressive disorder over the past quarter-century have been incremental rather than transformative, booster sessions have been proposed as a means of solidifying acute treatment gains and lowering relapse risk. However, evidence for the effectiveness of these treatment booster sessions remains inconclusive. This study therefore evaluated the long-term effectiveness of relapse prevention treatment booster sessions for major depression.MethodIn a two-arm, parallel-group, maintenance-phase randomized controlled trial (RCT) with repeated longitudinal measures, the sample consisted of participants in Sweden who had received acute treatment for depression (internet-based behavioral activation or physical activity) and were then randomly assigned to either an 8-week relapse prevention program (n = 119) or control group (n = 143). Participants were followed-up for 24-months with both monthly self-report questionnaires (Patient Health Questionnaire 9-item & Generalized Anxiety Disorder 7-item) and quarterly diagnostic interviews (Mini-International Neuropsychiatric Interview; MINI).ResultsBoth the relapse prevention group and control group exhibited similar depression-free trends over the course of the study period, with over 95% of participants in each group maintaining remission at the 24-month follow-up. Furthermore, all pre-hypothesized predictors of relapse were non-significant in differentiating the two groups at 24-month follow-up.DiscussionThese findings raise the question of whether treatment booster sessions are uniformly advisable for all mild–moderate cases of depression. For instance, preferentially recommending treatment boosters for psychotherapy-naïve individuals with depression may yield greater effects compared to individuals with difficult-to-treat depression. Our findings indicate that the efficacy of behavioral activation and physical activity may be even greater than previously reported, a testament to the lasting effects of internet-based psychotherapy.Clinical trail registrationClinicalTrials.gov, identifier NCT01619930.